2013
DOI: 10.1097/qad.0b013e32835cba6c
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Kaposi sarcoma during the first months on combination antiretroviral therapy

Abstract: Objective Determine if incident AIDS-defining Kaposi sarcoma (KS) or Pneumocystis jiroveci pneumonia (PJP) is associated with combination antiretroviral therapy (cART) initiation. Design Compare risk for KS and PJP by time on cART and CD4 reconstitution. Methods In the FHDH-ANRS CO4 cohort (N=66,369), KS (N=1811) and PJP (N=1718) incidence rates were computed by demographic and HIV strata. Crude and adjusted relative risk (RR) with 95% confidence intervals (CI) following cART initiation were calculated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
3
15
0
2
Order By: Relevance
“…11,12 As we demonstrate for the first time, the human papillomavirusrelated cancers (oropharyngeal, anal, cervical, and other genital cancers) had incidence patterns less distinctly associated with transplant intervals. After a human papillomavirus infection, immunosuppression is thought to increase the likelihood that the infection becomes persistent instead of being cleared.…”
Section: Discussionmentioning
confidence: 68%
“…11,12 As we demonstrate for the first time, the human papillomavirusrelated cancers (oropharyngeal, anal, cervical, and other genital cancers) had incidence patterns less distinctly associated with transplant intervals. After a human papillomavirus infection, immunosuppression is thought to increase the likelihood that the infection becomes persistent instead of being cleared.…”
Section: Discussionmentioning
confidence: 68%
“…It seems to exist an increased risk of SRI-SK in KS patients with lower median baseline CD4 [11,12], rapid increase in CD4 counts during the initiation of HAART [13], high HIV viral load [8], associated edema [13], clinical pretreatment of KS, detectable plasma HHV8 DNA and hematocrit <30% [8]. The risk of IRIS-SK is similar among different antiretroviral drug regimens [11] although Bower et al [13] reported a higher risk in those patients performing both major HAART classes together, protease inhibitors and non-nucleoside reverse transcriptase inhibitors, in a single regimen.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, they speculated that KS-IRIS is somewhat different from other forms of KS and therefore unique management strategies may be considered. Also, further studies on the mechanism of IRIS-SK are necessary as the response of HAART against HHV8 and AIDS-KS requires at least six months and, despite of this, the period of greatest risk of developing IRIS-SK is during the first 3 months of HAART [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported a high incidence of Kaposi sarcoma during the first 3 months of ART, describing KS as one of the manifestations of immune reconstitution inflammatory syndrome (IRIS) [ [12]. In our study, the median time from ART initiation to KS diagnosis was 5 months (IQR 0-39); roughly half of our patients who were on ART (10/19) were in virological failure at the time of KS diagnosis and in the other 9/19 patients KS could have been an IRIS manifestation.…”
Section: Discussionmentioning
confidence: 99%